Argonaute1 and Gawky Are Required for the Development and Reproduction of Melon fly, Zeugodacus cucurbitae - Jamil, Momana; Ahmad, Shakil; Ran, Yingqiao; Ma, Siya; Cao, Fengqin; Lin, Xianwu; Yan, Rihui (Frontiers in Genetics, 2022)
Argonaute family genes encode a highly conserved group of proteins that have been associated with RNA silencing in both animals and plants. This study investigates the importance of Argonaute1 (Ago1) and Gawky genes in the post-embryonic and ovarian development of the melon fly, Zeugodacus cucurbitae. The expression levels of these genes were mapped in all developmental stages and different adult tissues. Their roles in development were investigated using RNA interference (RNAi) via two different dsRNA delivery techniques, injection and oral feeding. A wide range of phenotypes were observed on segmentation, pigmentation, and ovarian development. RNAi-mediated silencing of Gawky caused high mortality and loss of body segmentation while Ago1 knockdown affected ovarian development and pigmentation. Developmental abnormalities and ovarian malformations caused by silencing these genes suggest that these genes are crucial for viability and reproductive capacity of Z. cucurbitae and may be used as potential target genes in pest management.